Review of the book: Distant Love. Models of living in the global era by Ulrich Beck and Elisabeth Beck-Gernsheim. Cambridge 2014, 220 pp. - Zalewska, Sabina (Uniwersyteckie Czasopismo Socjologiczne, 2016)
This book tackles a problem which is very important from the point of view of a contemporary researcher and observer of marriage and family relationships. It will also be of interest for an observer of social changes. More and more often one may hear about problems ensuing from breaking up of multicultural and multinational relationships. About problems with setting up the custody over minors, intra-family kidnapping and the discrepancies in parental rights in the parents’ countries of origin. It is becoming an element of reality in the global world.